OBSERVATIONAL STUDY ON SHOPHOUSE CONFIGURATIONS ADAPTABILITY IN PENANG, MELAKA, MUAR, AND KUALA LUMPUR: DESIGN PREFERENCES, AESTHETIC APPEAL, AND SOCIAL COHESION - Nur Amalina binti; Leng Pau Chung (Journal of Architecture, Planning and Construction Management, 2025)
Malaysian shophouses are vital cultural assets, embodying the nation's architectural and socioeconomic history. However, rapid urban development and changing lifestyles threaten their preservation, often prioritising modernisation at the expense of heritage. A critical issue is the lack of empirical research on how design alterations affect user satisfaction and social cohesion, leading to ad-hoc renovations that may erode their historical value while failing to meet contemporary needs. Many modified shophouses struggle to balance functionality, thermal comfort, and community engagement, risking their role as social hubs in urban neighbourhoods. This study investigates these challenges by analysing design adaptations, aesthetic preferences, and social impacts in shophouses across Penang, Melaka, Muar, and Kuala Lumpur. Through observational methods and matrix analysis, it assesses spatial layouts, materials, and user interactions. Findings reveal that hybrid designs—combining heritage features with modern upgrades—are most effective, strategically using double-skin façades, open spaces, and communal corridors to enhance liveability and social cohesion. The study advocates for evidence-based design strategies to ensure shophouses remain sustainable, culturally resonant, and socially inclusive.